Policies for achieving science excellence - Rowarth, Jacqueline (New Zealand Science Review, 2015)
​Achieving excellence in scientific research is a goal for many countries, resulting in a considerable amount of well-meaning research, policy setting and commentary around funding, education and management. Much of this has originated in New Zealand and, indeed, has been published in this journal. The history can be tracked through authors such as Edmeades (2004), Weir (2006) and Rowarth (2009), plus many editorials and initiatives such as the Science Manifesto by the National Science Panel (2008). Despite these efforts, the science system in New Zealand is not flourishing, and the ramifications are in the schools: assessment of school students’ attitudes to science/mathematics via the international comparisons TIMSS (The Trends in International Maths and Science Study) and PISA (Programme for International Student Assessment) indicates that New Zealand students do not like learning science/mathematics as much as their international counterparts, and see less value in learning these subjects (Buntting et al. 2013). Science and mathematics are, however, increasingly regarded as the foundation for employment. The Brookings report on the Hidden STEM (science, technology, engineering and mathematics) Economy makes the point clear: 20% of all jobs require a high level of knowledge in any one STEM field; half of all the STEM jobs are available to workers with sub-degree qualifications (Rothwell 2013). This article was prompted by the announcement by Minister of Science and Innovation, the Hon Steven Joyce, on Saturday 26 September 2015 that ‘Crown research institutes are about commercial science – that’s why they’re there. The pure science tends to be done more at universities’. This statement was followed by a public response from the President of the Association of Scientists, Dr Nicola Gaston, indicating the wider operational principles of Crown research institutes (CRIs) to undertake research for the benefit of New Zealand and pursue excellence in all its activity and not simply narrowly defined commercial science.